Mild Viral Gastroenteritis and Afebrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Ictal electroencephalograms (EEGs) were recorded in six patients (2 male, 4 female; ages 14 mo to 38 mo) with afebrile convulsions and mild gastroenteritis (CwG), in a study at Nagoya, Japan. None had febrile convulsions.